ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI PADI SAWAH SISTEM HAMBUR BENIH LANGSUNG DI DESA DOLAGO KECAMATAN PARIGI SELATAN KABUPATEN PARIGI MOUTONG - Munizar, Andi; Tangkesalu, Dance (AGROTEKBIS, 2019)
This study aims to analyze the income and feasibility of lowland rice farming system on direct spreading seed system. This research has been conducted from July to August 2017. Determination of location is done by purposively with the consideration that Dolago Village is one of rice production area with productivity of 5.09 ton/ha. Respondent determination was done by using simple random sampling method (Simple Random Sampling). Samples taken as many as 31 respondents of farmers' households from rice farmer population in Dolago Village as many as 108 farmers /household with error rate (15%) who work on  paddy. The analysis used in this research is income analysis (π) and feasibility (R/C-ratio). The result of the analysis showed that the average income of rice farmer in one season planting season in Dolago Village is Rp. 10.759.370/1.25ha/ Season Planting or Rp. 8.607.496/ha/ Season Planting. The results showed that Revenue of Cost Ratio (R/C) of lowland rice farming system of direct seeding system in Dolago Village, South Parigi Subdistrict of Parigi Moutong Regency is feasible to be cultivated. This is evidenced by the value (R/C) obtained by 2.21. This means that every expenditure of Rp. 1 will generate revenue of Rp. 2.21.